Legislation for Women Rights in PMLN and PTI Governments: A Comparative Analysis - Butt, Muhammad Waqas; Hasan, Saira; Khushnood, Qirat (Annals of Human and Social Sciences, 2024)
This study compares the legislative initiatives for women's rights implemented by the PMLN and PTI authorities in Pakistan from 2013 and 2022. Using a wealth of legislative documents, statements of policy, and academic analyses, this study identifies significant legislative achievements made by the PTI and PML-N administrations in tackling issues of discrimination, gender-based violence, and socioeconomic inequality that impact women in Pakistan. Through placing the comparison of results within the theoretical framework about liberal feminism, this study advances our comprehension of the intricacies inherent in the debate around women's rights in Pakistan. Content analysis is a research tool has been used within some given qualitative data. While acknowledging the progress made by both the PML-N and PTI governments in enacting laws aimed at safeguarding women's rights, The results show that the PMLN administration has achieved greater headway in attaining legislative program goals, but the PTI government's measures on women's rights are being criticized.